Increased C-reactive Protein Levels during Short-term Hormone Replacement Therapy in Healthy Postmenopausal Women - van Baal, Marchien W.; Kenemans, Peter; van der Mooren, Marius J.; Kessel, Hilda; Emeis, Jef J.; Stehouwer, Coen D. A. (Thrombosis and Haemostasis, 1999)
Objective: To study the short-term effect of unopposed oestradiol (E2) and sequentially combined hormone replacement therapy (E2 + P) on C-reactive protein (CRP) in healthy postmenopausal women. Design: Prospective, randomised, placebo-controlled 12-week study. Sixty healthy, normotensive, non-hysterectomised postmenopausal women received either placebo (N = 16) or daily 2 mg micronised oestradiol, either unopposed (N = 16, E2 group) or sequentially combined with a progestagen on 14 days of each cycle (N = 28, E2+P group). Data were collected at baseline and at 4 and 12 weeks. Results: CRP levels increased significantly during the 12 weeks in the E2 and the E2+P groups compared to placebo. No differences were found between the E2 group and the E2+P group [E2 and E2+P group together (N = 44) versus placebo: P = 0.01; E2 versus E2+P: P = 0.75]. To give a quantitative estimate of the increase, the median change calculated from baseline in both treatment groups together was +87% (P = 0.02) at 4 weeks, and +114% (P = 0.08) at 12 weeks, as compared to the placebo group. Conclusion: In healthy postmenopausal women, short-term treatment with E2 or E2+P was associated with a rapid rise in CRP concentrations. These observations raise the possibility that the increased risk of cardiovascular events is related to an initial increase in CRP levels after starting hormone replacement therapy.